1996
DOI: 10.1007/bf02447647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the parathyroid hormone—Calcium system on functional activity of the hypothalamus-neurohypophysis complex

Abstract: The effect of single and repeated parenteral administration of parathyroid hormone on the protein synthesis in neurosecretory cells of the supraoptic nucleus and on the blood vasopressin content is studied. The hormone enhances the synthesis of RNA in the supraoptic nucleus and the blood vasopressin content, particularly after a single administration.Key Words: parathyroid hormone; calcium; vasopressin; RNA; hypothalamus; neurohypophysis Although the effect of parathyroid hormone (PTH) on various organs and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Arterial stiffness and endothelial dysfunction have been observed in patients with primary hyperparathyroidism and may result in cognitive impairment [ 47 ]. PTH crosses the blood-brain barrier and PTH excess in animal models has been linked to enhanced release of vasopressin and vasoconstriction [ 48 ]. Additionally, hypoperfusion in several cortical regions involved in memory and learning has been observed in patients with primary hyperparathyroidism compared to controls [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arterial stiffness and endothelial dysfunction have been observed in patients with primary hyperparathyroidism and may result in cognitive impairment [ 47 ]. PTH crosses the blood-brain barrier and PTH excess in animal models has been linked to enhanced release of vasopressin and vasoconstriction [ 48 ]. Additionally, hypoperfusion in several cortical regions involved in memory and learning has been observed in patients with primary hyperparathyroidism compared to controls [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, we suggest that control of PTH levels may be important for protecting against age-induced dementia. PTH's potential involvement with dementia may be explained in the following way: PTH has been shown to cross the blood-brain barrier [ 26 ]. PTH has been considered a candidate risk factor for senile dementia because sustained high levels of PTH in the brain may cause degeneration of specific brain regions due to Ca(2+) overloading [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence also suggest that PTH may directly affect neurovascular integrity independent of vitamin D homeostasis. PTH has been shown to cross the BBB and an exaggerated level of PTH within CSF appears to cause neuronal degeneration due to cellular iCa overloading [ 33 , 34 ]. In clinical studies, increased levels of PTH have been reported as an independent risk factor of age-related cognitive decline [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%